Digital Transformation and Business Competition Challenges Comparative Analysis of Antitrust Law - Kartikawati, Dwi Ratna (PT. Riset Press International, 2024)
Digital transformation has changed the business competition paradigm by enabling the growth of the digital economic industry. However, this also creates new problems related to market domination by large companies and restrictions on access to platforms, making market penetration difficult for small and medium businesses. The antitrust legal framework in Indonesia needs to be strengthened to face the challenges of globalization and digital transformation. Implementation of Law Number 5 of 1999 still faces obstacles in dealing with monopolistic practices and abuse of dominant positions by large companies. Therefore, revisions or additions to more specific regulations are needed. Business competition in the digital economy is characterized by unequal access and abuse of market power by large technology companies, hindering innovation and creating injustice. Concrete steps are needed to improve the fairness of business competition, including increased regulation and more effective law enforcement. This research uses descriptive normative legal research methods to analyze the implementation of antitrust law in facing challenges arising from digital transformation. By focusing on the description and analysis of legal norms relating to business competition, this research explores how these norms are interpreted and applied in everyday legal practice. Antitrust law in Indonesia needs to be adapted to the realities of the digital economy to ensure optimal protection against business competition. This includes increasing the capacity of business competition supervisory institutions, expanding the scope of regulations to cover online platforms, and increasing sanctions for violators. Thus, it is hoped that this adjustment can provide more effective protection for small and medium businesses and encourage innovation in the digital economy sector.